Measuring social capital of healthcare organizations reported by employees for creating positive workplaces - validation of the SOCAPO-E instrument - Lena Ansmann; Kira Isabel Hower; Markus Antonius Wirtz; Christoph Kowalski; Nicole Ernstmann; Lorna McKee; Holger Pfaff (BMC, 2020)
Abstract Background In highly segmented and complex healthcare organizations social capital is assumed to be of high relevance for the coordination of tasks in healthcare. So far, comprehensively validated instruments on social capital in healthcare organizations are lacking. The aim of this work is to validate an instrument measuring social capital in healthcare organizations. Methods This validation study is based on a cross-sectional survey of 1050 hospital employees from 49 German hospitals which specialize in breast cancer care. Social capital was assessed by a six-item scale. Reliability analyses and confirmatory factor analyses were conducted to determine the content validity of items within the theory-driven one-dimensional scale structure. The scale's associations with measures of the social aspects of the work environment (identification, social support, open communication climate) were estimated to test convergent validity. Criterion-related validity was evaluated by conducting structural equation modelling to examine the predictive validity of the scale with measures of work engagement, well-being and burnout. Results A one-dimensional structure of the instrument could be identified (CFI = .99; RMSEA = .06). Convergent validity was shown by hypothesis-consistent correlations with social support offered by supervisors and colleagues, a climate of open communication, and employee commitment to the organization. Criterion-related validity of the social capital scale was proved by its prediction of employee work engagement (R 2 = .10-.13 for the three subscales), well-being (R2 = .13), and burnout (R 2 = .06-.11 for the three subscales). Conclusions The confirmed associations between social capital and work engagement, burnout as well as well-being stress the importance of social capital as a vital resource for employee health and performance in healthcare organizations. In healthcare organizations this short instrument can be used as an efficient instrument to measure the organizations' social capital.